Negative modulation of SA signaling components by the capsid protein of tobacco mosaic virus is required for viral long-distance movement - Venturuzzi, Andrea Laura; Rodriguez, Maria Cecilia; Conti, Gabriela; Leone, Melisa; Caro, Maria Del Pilar; Montecchia, Juan Francisco; Zavallo, Diego; Asurmendi, Sebastian (Wiley, 2024)
An important aspect of plant–virus interaction is the way viruses dynamically move over long distances and how plant immunity modulates viral systemic movement. Salicylic acid (SA), a well-characterized hormone responsible for immune responses against virus, is activated through different transcription factors including TGA and WRKY. In tobamoviruses, evidence suggests that capsid protein (CP) is required for long-distance movement, although its precise role has not been fully characterized yet. Previously, we showed that the CP of Tobacco Mosaic Virus (TMV)-Cg negatively modulates the SA-mediated defense. In this study, we analyzed the impact of SA-defense mechanism on the long-distance transport of a truncated version of TMV (TMV ∆CP virus) that cannot move to systemic tissues. The study showed that the negative modulation of NPR1 and TGA10 factors allows the long-distance transport of TMV ∆CP virus. Moreover, we observed that the stabilization of DELLA proteins promotes TMV ∆CP systemic movement. We also characterized a group of genes, part of a network modulated by CP, involved in TMV ∆CP long-distance transport. Altogether, our results indicate that CP-mediated downregulation of SA signaling pathway is required for the virus systemic movement, and this role of CP may be linked to its ability to stabilize DELLA proteins.